ANALISIS PENGENDALIAN PERSEDIAAN BARANG DAGANG PADA UD. HADI FAJAR SAMARINDA - Razikin, Chaeri (EKONOMIA, 2012)
A large number of inventory items result in booking fees as well as the cost of inventory items to be great storage which certainly reduces the profit which should be achieved by the company. Otherwise inventory items that are too small result in purchases the higher frequencies, consequently the costs related to the purchase of such goods are high anyway.While the number of needs based on estimates and the experience that has been done so far. Bookings made uncertain because the company saw supplies there were still in the warehouse.Actually the latest ceramic plates are still can be pressed through a proper inventory models. Along with the it companywill certainly be confronted with the problem of waste costs over the supplies that resulted in declining profits gained as a result of these inefficiencies.This research aims to find out how the large amount of economical order supplies ceramic plates Sango 9 "A-002 and Vicenza 9" Lis Mas DP 9 for each frequency of the orders can be done by UD. Hadi Fajar in Samarinda.In anticipation of the inventory in the warehouse as required then needed aanalysis of the minimum inventory control at minimal cost. By using the method of calculation of EOQ to research data such as storage costs, fees, prices and number of sales of ceramic plates Sango 9 "A-002 and Vicenza 9" Lis Mas DP 9 at UD.